2009
DOI: 10.1093/humrep/dep259
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative use of oral contraceptive pills for prevention of anatomical relapse or symptom-recurrence after conservative surgery for endometriosis

Abstract: Long-term OCP therapy can be a reliable adjuvant post-operative measure to prevent or reduce frequency/severity of recurrent dysmenorrhoea and anatomical relapse of endometriosis. Since both continuous and cyclic OCP administration regimens seem to have comparable effects, the choice of regimen can be modulated according to patient preferences. The protective effect seems to be related to the duration of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
10

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 28 publications
2
52
0
10
Order By: Relevance
“…Some studies have reported that monophasic oral contraceptive treatment either to reduce retrograde menstrual cycles or to inhibit ovulation-which are both considered etiopathogenetic factors for endometriosis-may also suppress the recurrence of endometrioma when administered long term after conservative surgery [2,5,10,16,23]. Progestogens have a crucial role in decreasing endometriotic lesions, through a number of mechanisms which may vary in type and intensity according to the different molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported that monophasic oral contraceptive treatment either to reduce retrograde menstrual cycles or to inhibit ovulation-which are both considered etiopathogenetic factors for endometriosis-may also suppress the recurrence of endometrioma when administered long term after conservative surgery [2,5,10,16,23]. Progestogens have a crucial role in decreasing endometriotic lesions, through a number of mechanisms which may vary in type and intensity according to the different molecules.…”
Section: Introductionmentioning
confidence: 99%
“…(24) Our result supported the evidence that chronic pelvic pain related to endometriosis may respond partially to anti-prostaglandins and oral contraceptive pills, the facts proved by others. (25,26) In our study, the responds rate to NSAIDS and hormonal therapy was 31.3%. Studies have shown that if these agents are refractory, endometriosis is diagnosable in 50% to 70% of these patients.…”
Section: Discussionmentioning
confidence: 47%
“…Conservative surgical procedures like adhesiolysis and removal of endometriotic cysts with post-operative medical therapy with OCP for more than a year can give longer duration of pain relief and delay the anatomical recurrence rates. [16][17][18][19] The studies in the Table 8 include observational studies, randomized controlled studies and non-randomized studies.…”
Section: Discussionmentioning
confidence: 99%